Flow battery production: Materials selection and environmental impact. (1st October 2020) - He, Haoyang; Tian, Shan; Tarroja, Brian; Ogunseitan, Oladele A.; Samuelsen, Scott; Schoenung, Julie M.
Abstract: Energy storage systems, such as flow batteries, are essential for integrating variable renewable energy sources into the electricity grid. While a primary goal of increased renewable energy use on the grid is to mitigate environmental impact, the production of enabling technologies like energy storage systems causes environmental impact. Thus, understanding the impact of producing energy storage systems is crucial for determining the overall environmental performance of renewable energy from a systems perspective. In this study, the environmental impact associated with the production of emerging flow battery technologies is evaluated in an effort to inform materials selection and component design decisions. The production of three commercially available flow battery technologies is evaluated and compared on the basis of eight environmental impact categories, using primary data collected from battery manufacturers on the battery production phase including raw materials extraction, materials processing, manufacturing and assembly. In the baseline scenario, production of all-iron flow batteries led to the lowest impact scores in six of the eight impact categories such as global warming potential, 73 kg CO2 eq/kWh; and cumulative energy demand, 1090 MJ/kWh. While the production of vanadium redox flow batteries led to the highest impact values for six categories including global warming potential, 184 kg CO2 eq/kWh; and cumulative energy demand, 5200 MJ/kWh. Production of zinc-bromine flow batteries had the lowest values for ozone depletion, and freshwater ecotoxicity, and the highest value for abiotic resource depletion. The analysis highlight that the relative environmental impact of producing the three flow battery technologies varies with different system designs and materials selection choices. For example, harmonization of the battery system boundary led to freshwater eutrophication and freshwater ecotoxicity values for vanadium redox flow batteries lower than the values for zinc-bromine flow batteries. Regarding alternative material use strategies, we conclude that vanadium redox flow batteries exhibit the lowest potential in four of the eight impact categories including global warming potential at 61 kg CO2 eq/kWh. In zinc-bromine flow batteries, the titanium-based bipolar plate contributes higher environmental impact compared to carbon-based materials, and the polymer resins used in all-iron flow batteries could be replaced with material with lower potential for ecotoxicity. Overall, the analysis reveals the sources of potential environmental impact, due to the production of flow battery materials, components and systems. The findings from this study are urgently needed before these batteries become widely deployed in the renewable energy sector. Furthermore, our results indicate that materials options change the relative environmental impact of producing the three flow batteries and provide the potential to significantly reduce the environmental impact associated with flow battery production and deployment. Graphical abstract: Image 1 Highlights: Environmental impact assessment of flow battery production was conducted. Three types of flow batteries with different design parameters were analyzed. Design factors and materials choices largely affect the environmental impact. Choices fr cell stack, electrolyte and membrane materials influence total impact. Design of accessories and balance of plant can reduce environmental impact.